PENERAPAN FUZZY MADM DENGAN METODE SAW UNTUK PEMILIHAN KEPALA LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT - Gunardi Hamza (Riau Jurnal Teknik Informatika, 2025)
The quality and ability of man is a very important aspect in an agency/company. Management and control of which both strongly influenced aspects of success. If a leader can do very well with the management, the expected number of agencies/companies can run all the process of with good anyway. From issue in assessing the performance of a person is something difficult to avoid. Quantitative assessments often lead to disappointment because the parameters there are hard to measure. To be able to process the data more objective assessment then needed a Decision Support System (DSS) that can determine who's worth was made a candidate for the head of the institution, at the same time avoiding and reducing manual calculations are used, then with computerization can help troubleshooting establishments/companies that frequently occur, but still needs human judgement in applying the solution. The method used for selecting the prospective head of Institution is Fuzzy Multiple Attribute Decision Making (FMADM) Simple Additive Weighting (SAW), because this method is to determine the value of the weighting on each attribute and continued with stages of the rank to choose the best alternative, what is meant is the specified terms.